Improving Ultrasound Diagnostics For Acute Spermatic Cord Cysts (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Testicular torsion is a surgical emergency that is caused by twisting of the spermatic cord and its content. This condition causes irreversible changes after 6 hours. Early recognition and management of testicular torsion is important for testicular salvage and preservation of fertility.